Optimizing Chinese hamster ovary cell line development via targeted control of N-glycosylation. (November 2015) - Alves, Christina S; Prajapati, Shashi
The glycosylation profile of a protein is vital to its success as a biotherapeutic as it affects its efficacy and function and, thus, has been extensively studied for proteins produced in Chinese hamster ovary cells. Improvements in the sensitivity and throughput of various analytical assays have allowed for more accurate glycosylation information earlier in the cell line development process. Bioprocess parameters and media additives have been used to modulate the glycosylation of proteins. Genome editing techniques have enabled the regulation of glycosylation genes to achieve a targeted glycan profile. This review highlights advances made in engineering strategies and improvements in high-throughput N-glycan assessment that allow for generation of high-productivity clones with a specific product quality profile.